Shipping Industry in India Colonialism to globalisation (a spatio-temporal analysis) - Gupta, Sadanand (New Delhi Pentagon, 2016)
Seaports represent a complex interplay of physical, spatial and socio-economic phenomena and are invariably the knots/centres where the different kinds of interactions and dependencies in the supra-national economy are worked out, be it in the past under colonialism or under the modern phase of 'globalisation'. The book is an attempt to present the concepts and theoretical frameworks relevant to the historical and spatial analysis of the seaports, port systems and port-cities. This is necessary because most of the concepts have acquired varying theoretical meanings in social science and port planning literature; a detailed outline on the evolution of the Indian seaport system from the colonial period, when the introverted economy of the country was reoriented and focused on the seaports, to the present day, when India is being increasingly drawn into the world economy requires an analysis, which has been done on the Indian port-cities within the national systems of the ports and cities and thus outlines the linkages between the port and city functions. This also underlines the various factors that have historically influenced the performance, management and future prospects of the Indian seaports.
Keywords: Harbours-India; Shipping Industry-India; Ports-India; IAS as an author; Civil Servant